18.1: Invited Paper: Color Electronic Paper and Applications. (4th October 2019) - Wang, Xidu; Hu, Dianlu; Chen, Yu; Zeng, Xi; Yang, Paul
Abstract : Electronic Paper (EPD) is well known in reading area, such as amazon's kindle. But it is still monochrome after more than 10 years' development. The main changes are adding touch and front light, and making it more high resolution. Color EPD is required by consumers for a long time, especially in the education area. The reasons why it is so difficult for color EPD to come to market will be discussed. And some methods for realizing color EPD will be also shown. Color EPD is not far away from us, new applications are on the way. Some of these cases will also be introduced in this paper.